The days of the Society of Jesus: A historical portrait from its origins - Burrieza Sánchez, Javier (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
In Ignatius of Loyola, founder of the Society of Jesus, there are represented successively three different men of the 16th-century: one who sought to rise in social esteem, one who repented of his past life, and finally one who discovered a religious vocation and later became the superior of an order that he founded, the Society of Jesus. This article emphasizes how the culture of the 16th-century influenced the foundation of this religious order. It was a century of establishing modern states, geographical discoveries, debates and religious reformation, editorial successes, the use of the printing press in the spreading of Humanism. All that had an outstanding influence on the different ministries that were developed: preaching sermons, spiritual direction, teaching, visits to prisons and hospitals, social rehabilitation and missions.